Fluctuating fluid flow and heat transfer of an obliquely impinging air jet - MURRAY, DARINA (My University, 2008)
Heat transfer to an obliquely impinging air jet is investigated experimentally. Distributions of the mean and the fluctuating component of the surface heat transfer are reported for a jet Reynolds number of 10,000, nozzle to impingement surface distance, H/D, from 2 to 8 and angle of impingement, a, from 30 to 90 (normal impingement). Flow velocity measurements along the impingement surface are related to heat transfer distributions. At specific locations the surface heat transfer and the local fluid velocity are measured simultaneously and coherence and phase difference information between the signals are reported. The vortical characteristic of the flow is shown to vary considerably with the angle of impingement; depending on the distance between the near nozzle edge and the impingement surface, vortices at different stages of development impact with the target surface. The influence of naturally occurring vortices in an impinging jet flow on the magnitude of heat transfer in the near wall jet is reported.
PUBLISHED
Keywords: Oblique jet impingement; Coherence; Phase difference; Vortices